DIMENSIONS UNDERLYING PLACE IDENTITY FOR SUSTAINABLE URBAN DEVELOPMENT - Ernawati, Jenny (MATTER: International Journal of Science and Technology, 2018)
In the last thirty years, the identity of a place (place identity) has become an important issue in urban planning and design. In line with the global movement to protect places which has a significant cultural heritage, then concerns about the loss of individuality and distinctiveness between one place and another as the impact of globalization increased. This paper, therefore, meant to present the results of research intended to explore dimensions underpinning peoples evaluations of place identity. This study used a quantitative approach by applying the survey research method. The town of Malang chosen as the research locus. The instrument used to collect the data is a self-administered questionnaire using a Likert scale. A total of 240 respondents were selected randomly from the list of residents of Malang phonebook. The concept of place identity is evaluated based on five aspects: familiarity, attachment, commitment, continuity, and external evaluation. Dimensions that underlying place identity, based on communitys assessments, are revealed through factor analysis. Results of the study show there are three dimensions underlying communitys evaluations of place identity, i.e., Personal Relationship, Physical Environment, and Commitment. Further research is needed to elaborate the three underlying dimensions of the place identity.